Diet and predation risk affect tissue and excretion nutrients of Trinidadian guppies: a field survey - Eugenia Zandonà; Karen E. Sullam; Christopher M. Dalton; Rana W. El-Sabaawi; Susan S. Kilham; Alexander S. Flecker (Scientific Reports)
Abstract Consumers vary in their excretion of nitrogen and phosphorus, altering nutrient cycles and ecosystem function. Traditional mass balance models that focus on dietary and tissue nutrients have poorly explained such variation in excretion. Here, we contrast diet and tissue nutrient models for nutrient excretion with predation risk, an often overlooked factor, using the Trinidadian guppy (Poecilia reticulata) as our model system. We surveyed guppies at 12 sites spread across two streams with parallel gradients in food quality and predation risk. At each site, we assessed guppy diet, tissue nitrogen (N), and phosphorus (P) content, and N and P excretion. Predation risk best explained guppy excretion, especially P: guppies excreted less in sites with a dominant predator, while traditional models for excretion rate based on diet quality and tissue nutrients failed to explain it. Guppy tissue N (but not P) most closely correlated with guppy diet quality, showing evidence for flexible homeostasis. Our work extends previous laboratory studies’ results to natural streams and shows that predation risk alters feeding behavior and physiology, driving substantial variation in guppy nutrient, particularly P, excretion rates. We suggest that predation risk is an important factor determining nutrient excretion variation, warranting further attention. Our results also show that tissue nutrients and excretion nutrients are decoupled.